STUDI TENTANG NILAI – NILAI PANCASILA YANG TERKANDUNG DALAM KESENIAN LENGGER KECAMATAN BANDAR SEIKIJANG KABUPATEN PELALAWAN - khoiri, M.khoiri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSRACT : The research was motivated by the values contained in Pancasila Lengger in District Seikijang Kingdom, which in the arts there Lengger solidarity and strengthen friendship society, as a means of education and teaching to the community.. Formulation of the problem in this research is Is there Pancasila values contained in Lengger Bandar Seikijang Regency Pelalawan District Seikijang . This study aims to analyze whether there Pancasila values contained in Lengger Regency Pelalawan District Seikijang. Associated with the cultural foundation of Pancasila Notonegoro (1991) argues that values are strung or into a system that, as with the basic values of Pancasila, usually sourced from cultural and historical experiences of a people who created the ideological it. This research the author carried on in Kecamatan Bandar Seikijang Kab. Pelalawan lasts of month of in December 2014 until is completed research. Population in this research is the entire society Bandar Seikijang who domiciled in Kecamatan Bandar Seikijang who numbered 16,784 person. The sampling technique is Purposive Sampling, the sample in this study was 377 X 20%. So the sample size in this study as many as 75 people. Data collection techniques used were in the form of observation techniques, interviewing techniques, technical documentation, technical and engineering literature study questionnaire. In analyzing the data using descriptive qualitative method. The hypothesis in this study is There Pancasila values in Lengger in District Seikijang Regency Pelalawan. These results indicate that There Pancasila values in Lengger in District Seikijang Regency Pelalawan. with a percentage of 59.6% and included into the benchmark categorized as "Yes" is the benchmark of 50.01% -100%. So, the hypothesis : There Pancasila values in Lengger in District Seikijang Regency Pelalawan. is received.Keywords: Pancasila values, Lengger